2018
DOI: 10.4162/nrp.2018.12.3.199
|View full text |Cite
|
Sign up to set email alerts
|

GABA-enriched fermented Laminaria japonica improves cognitive impairment and neuroplasticity in scopolamine- and ethanol-induced dementia model mice

Abstract: BACKGROUND/OBJECTIVESFermented Laminaria japonica (FL), a type sea tangle used as a functional food ingredient, has been reported to possess cognitive improving properties that may aid in the treatment of common neurodegenerative disorders, such as dementia.MATERIALS/METHODSWe examined the effects of FL on scopolamine (Sco)- and ethanol (EtOH)-induced hippocampus-dependent memory impairment, using the Passive avoidance (PA) and Morris water maze (MWM) tests. To examine the underlying mechanisms associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…Moreover, the Gaba-enriched fermented Laminaria japonica (GFL) provided a protective effect against cognitive impairment associated with dementia in the elderly [25]. In addition, Reid and colleagues have shown that GFL could improve cognitive impairment and neuroplasticity in scopolamine- and ethanol-induced dementia model mice [26]. Especially, GFL was effective in increasing serum brain-derived neurotrophic factor level that associated with lower risk for dementia and Alzheimer’s disease in middle-aged women [27].…”
Section: Pharmaceutical Properties Of Gabamentioning
confidence: 99%
“…Moreover, the Gaba-enriched fermented Laminaria japonica (GFL) provided a protective effect against cognitive impairment associated with dementia in the elderly [25]. In addition, Reid and colleagues have shown that GFL could improve cognitive impairment and neuroplasticity in scopolamine- and ethanol-induced dementia model mice [26]. Especially, GFL was effective in increasing serum brain-derived neurotrophic factor level that associated with lower risk for dementia and Alzheimer’s disease in middle-aged women [27].…”
Section: Pharmaceutical Properties Of Gabamentioning
confidence: 99%
“…It has been reported that FST supplementation reduce obesity and improve stress management [29]. Furthermore, previous studies have shown that FST can protect against age-associated short-term memory loss and reduced physical functioning [30,31,32]. However, the effect of FST on bone has not previously been investigated and therefore we decided to investigate whether FST had any inhibitory effect on RANKL-stimulated osteoclast differentiation using RAW 264.7 mouse macrophage cells.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we utilized the passive avoidance and Y-maze tests to assess fear-motivated memory retrieval [36] and spatial learning/memory in mice, respectively [37]. Results on these behavioral tests have been associated with damage to the cholinergic system in areas of the basal forebrain such as the hippocampus and cortex [38,39,40]. Ach, which is hydrolyzed by AChE, is well-known enzyme which plays a pivotal role in learning and memory [41].…”
Section: Discussionmentioning
confidence: 99%